Paraguay : Fourth Review Under the Stand-By Arrangement and Request for Waiver of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Paraguay's Fourth Review Under the Stand-By Arrangement and Request for Waiver of Performance Criteria are examined. The main challenge is to consolidate the macroeconomic gains achieved thus far and deepen structural reform. A stable macroeconomic environment will be the key for creating the conditions for sustainable growth and poverty reduction. Although all areas of structural reform are important, public banking reform has proved to be difficult, and its implementation will signal the resolve of the authorities to carry on with the reform agenda.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet